2021
DOI: 10.3390/molecules26010212
|View full text |Cite
|
Sign up to set email alerts
|

Selective Extraction of Sinapic Acid Derivatives from Mustard Seed Meal by Acting on pH: Toward a High Antioxidant Activity Rich Extract

Abstract: The aim of this paper is to study the effect of the pH on the extraction of sinapic acid and its derivatives from mustard seed meal. Solutions of acidic pH (pH 2), basic pH (pH 12) and distilled water (uncontrolled pH ~ 4.5) were tested at different percentages of ethanol. The maximum extraction yield for sinapic acid (13.22 µmol/g of dry matter (DM)) was obtained with a buffered aqueous solution at pH 12. For ethyl sinapate, the maximum extraction yield reached 9.81 µmol/g DM with 70% ethanol/buffered aqueous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 39 publications
(35 reference statements)
1
14
0
Order By: Relevance
“…The quantitative profile of phenolics in broccoli stalks and sub-tissues is in agreement with what was studied in broccoli by-products, also stabilized by applying lyophilization processes and, thereby, exposed to similar deleterious effects, where there is also a predominance of sinapic acid and derivatives, as well as, to a lesser extent, feruloyl derivatives [ 1 , 27 ]. This preponderance is of special relevance because of the strong radical scavenging activity demonstrated for sinapic acid derivatives, as well as their capacity to interact with the membrane lipids and, thus, participate in the prevention of lipid peroxidation [ 29 , 30 ]. These molecular capacities allow the envisaging of the application of the materials obtained as functional ingredients.…”
Section: Resultsmentioning
confidence: 99%
“…The quantitative profile of phenolics in broccoli stalks and sub-tissues is in agreement with what was studied in broccoli by-products, also stabilized by applying lyophilization processes and, thereby, exposed to similar deleterious effects, where there is also a predominance of sinapic acid and derivatives, as well as, to a lesser extent, feruloyl derivatives [ 1 , 27 ]. This preponderance is of special relevance because of the strong radical scavenging activity demonstrated for sinapic acid derivatives, as well as their capacity to interact with the membrane lipids and, thus, participate in the prevention of lipid peroxidation [ 29 , 30 ]. These molecular capacities allow the envisaging of the application of the materials obtained as functional ingredients.…”
Section: Resultsmentioning
confidence: 99%
“…The pH of extracting solvents can greatly influence the electrostatic and stability of organic compounds. Chadni et al (2021) showed that sinapic acid was a pH‐dependent phenolic compound, in which the highest amount (13.22 ± 0.44 μmol/g of dry matter) was recovered from a buffered aqueous solution at pH 12. Galano et al (2011) previously confirmed the structural transformation of sinapic acid under the influence of pH using the computational stimulation method.…”
Section: Extraction Of Mustard's Major Sinapatesmentioning
confidence: 99%
“…[36][37][38] Hydroxycinnamic acids can be efficiently extracted from woody biomass with purities of up to 99%. Extraction can be conducted through alkaline [39][40][41][42] or enzymatic hydrolysis 43,44 followed by solvent extraction, 45,46 adsorption onto nanomaterials or membranes, 47,48 or counter-current chromatography (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%